PERSEPSI MAHASISWA AKUNTANSI TERHADAP ETIKA PROFESI DIPANDANG DARI SEGI GENDER PADA PERGURUAN TINGGI DI PURWOKERTO - Apriliastuti, Idnas (Kompartemen : Jurnal Ilmiah Akuntansi, 2017)
This study aims to examine whether there are differences in students perceptions of the accounting professional ethics in terms of gender. This study uses primary data collected by distributing questionnaires to selected respondents. The method used in sampling is purposive sampling with the criteria registered as accounting student at universities in Purwokerto, had taken auditing courses 1, an still be an active student at faculty of economics at universities in Purwokerto. The research hypothesis testing using statistical test is an independent sample t-test with a significant level of 0,05. The results and discussion of the research shows that a significant liability with a value of 0,980 is more than 0,05. Public interest with a significant value of 0,085 is more than 0,05. Integrity with a significant value of 0,249 is more than 0,05. Objectivity with a significant value of 0,758 more than 0,05. Competence and professional prudence with a significant value 0,695 more than 0,05. Confidentiality with a significant value of 0,567 is more than 0,05. Professional behavior with a significant value of 0,495 is more than 0,05. Technical standards with a significant value of 0,970 is more than 0,05. With this perception of the ethics of the proffesion of accounting stundents by gender differents significantly. Keywords : Perception, Students Accounting, Professional Ethics, and Gender